Islamic Child Parenting Practices and Muslim Family Resilience in Southeast Asia: A Systematic Literature Review - Dwinandita, Audrey (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – This study explores the integration of Islamic values in child parenting practices and its impact on family resilience within Muslim families in Southeast Asia. The necessity of this research arises from the increasing interest in how religious teachings influence family dynamics and child development, providing a unique perspective on parenting in diverse cultural contexts. Design/methods/approach – A systematic literature review methodology adhered to the PRISMA guidelines. Databases such as Scopus, Google Scholar, Emerald, PubMed, Taylor & Francis, Springer, and Semantic Scholar were searched using specific keywords related to Islamic parenting and family resilience in Southeast Asia. The study included peer-reviewed empirical research published between 2000 and 2024. From the results of the article selection, 39 articles were narrowed down and analysed to reveal various critical aspects of the research theme. Thematic analysis was conducted to identify, analyse, and report themes within the data. Findings – The review identified that integrating Islamic values into parenting practices significantly enhances family resilience, promotes interfaith tolerance, and supports children's moral development. Key themes included the implementation of wasatiyyah (moderation), character education based on Islamic teachings, and the role of community and cultural integration in parenting. However, challenges such as balancing cultural influences and addressing special needs within the context of Islamic parenting were also highlighted. Research implications/limitations – The study's limitations include the diverse cultural backgrounds of the families studied and the reliance on existing literature, which may affect the generalizability of the findings. Future research should consider longitudinal studies and examine the role of community support, religious institutions, and modern technology in parenting. Practical implications – This study provides valuable insights into the role of Islamic values in enhancing family resilience among Muslim families in Southeast Asia. It highlights the importance of religious teachings in shaping parenting practices and offers recommendations for future research and practical applications. Originality/value – This is your opportunity to provide readers with an analysis of the value of your results. It is a good idea to ask colleagues whether your analysis is balanced and fair, and again, it is essential not to exaggerate. You can also conjecture what future research steps could be. Paper type Literature review